2005
DOI: 10.1002/eji.200425746
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo expansion of human cytomegalovirus‐specific cytotoxic T cells by recombinant polyepitope: implications for HCMV immunotherapy

Abstract: Stem cell transplantation (SCT) remains the most effective curative therapy for the majority of hematopoietic malignancies. Unfortunately, SCT is limited by its toxicity and infectious complications that result from profound immunosuppression. In particular, acquisition of exogenous or reactivation of endogenous human cytomegalovirus (HCMV) is common after SCT. More recently, reconstitution of host immunity through augmentation of anti-HCMV T cell responses has been proposed as an exciting candidate therapy to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…7). This strategy dramatically increased the precursor frequency of antigen-specific T cells; however, the infusion of virus-specific T cells with single-epitope specificity may allow variants to (47,66,173,194,216,217,276). PE, phycoerythrin; PBMC, peripheral blood mononuclear cells.…”
Section: Exploiting Cellular Immune Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…7). This strategy dramatically increased the precursor frequency of antigen-specific T cells; however, the infusion of virus-specific T cells with single-epitope specificity may allow variants to (47,66,173,194,216,217,276). PE, phycoerythrin; PBMC, peripheral blood mononuclear cells.…”
Section: Exploiting Cellular Immune Responsesmentioning
confidence: 99%
“…22,2009 IMMUNE RESPONSE TO HCMV 89 escape and also limit the use of this technology to patients who carry a single HLA allele. More recently, the use of replication-deficient adenoviral vectors encoding multiple epitopes from HCMV have been used to expand specific T cells that recognize virally encoded antigens expressed at different stages of infection (e.g., early, IE, and late) (217,288) (Fig. 7).…”
Section: Exploiting Cellular Immune Responsesmentioning
confidence: 99%
“…The construction of the recombinant Ad5F35-based adenovirus has been described in our previous work (Rist et al, 2005). This vector expresses the CMV gB sequence from the alanine residue at position 31 to valine at position 700 with deletion of the signal sequence, and 46 contiguous HLA class I-and class II-restricted T-cell epitopes as a fusion protein (AdgBCMVpoly).…”
Section: Methodsmentioning
confidence: 99%
“…Ad-gBCMVpoly is a novel chimeric vaccine based on a replication-deficient adenovirus that encodes a truncated form of CMV-encoded gB antigen and multiple CMV Tcell epitopes from eight different CMV antigens, restricted through multiple human leukocyte antigen (HLA) class I and class II alleles, as a single fusion protein (Rist et al, 2005). Our most recent studies have demonstrated that immunization of an immunocompetent host with this chimeric vaccine consistently generated a pluripotent CMV antigen-specific cellular and antibody response, which provided protection against viral infection .…”
Section: Introductionmentioning
confidence: 99%
“…Research has shifted to development of subunit vaccines that contain the most important antigens and induce responses that will be protective in vivo. This can be designed to target specific T cell epitopes by using recombinant viruses containing minimal CMV epitopes linked together, such as the poly-epitope-based recombinant adenovirus vaccine [72]. This constitutes over 30 different immunogenic peptides derived from eight CMV antigens, restricted by 16 HLA types covering >90% of the population.…”
Section: Treatmentmentioning
confidence: 99%